An Open Electronic Prototyping Platform as Resource for Teaching - Egea, Rafael Rosa; Rosa, Renata Lopes; Rodríguez, Demóstenes Zegarra (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2017: Anais do XXVIII Simpósio Brasileiro de Informática na Educação, 2017)
The use of the Prototyping Platform Arduino has been very used in automation projects. In this study, the Arduino was used in classes of electronic laboratory. The purpose of the project is facilitating the students' learning with the use of a simple and didactic prototype and at the end of the course, to evaluate the knowledge of undergraduate students. Prior to the use of Arduino, other traditional electronic components were used in the laboratory to verify if the use of Arduino facilitated the learning in laboratory classes. The results showed that the use of Arduino facilitated the achievement of theoretical concepts by 30% compared to the use of traditional teaching modules for electronic.